Regional cooperation in South Asia : review of the SAARC. - WAGNER, Christian (1993)
Notes that until the mid-1980s, the political differences, bilateral conflicts and influence of the big powers prevented regional cooperation in South Asia. Presents an overview of the emergence of the SAARC, and a provisional review of the organisation.